Clinical and Pathological Features of Bovine Ischaemic Teat Necrosis. (October 2022) - Crosby-Durrani, Hayley E.; Carter, Stuart D.; Blundell, Richard J.; Manning, Al; Blowey, Roger; Evans, Nicholas J.
Summary: Bovine ischaemic teat necrosis (ITN) is an emerging disease of unknown aetiology affecting mostly dairy cows in the early stages of first lactation and a substantial welfare concern frequently leading to premature culling and economic losses. Specific diagnostic criteria are lacking. The aims of this study were to develop an appropriate ITN grading system, describe the histopathological changes and investigate the potential aetiological role of several pathogens in 47 cows with 73 ITN lesions from 28 farms. ITN lesions were allocated to one of three broad macroscopic categories: presence of a non-proliferative lesion on the teat (type 1); proliferative teat lesion with crusting (type 2); severe purulent to eosinophilic, ulcerative and necrotising dermatitis and sloughing or total absence of the teat (type 3). Lesions were mostly observed on the medial aspect of the teat but there was no anatomical predisposition as to which teats were more frequently affected. In approximately 50% of the ITN teats reviewed, the lesions were continuous with the skin of the udder and 34.2% of cases had sloughed or partially sloughed teats. The main histological findings were: focally extensive severe purulent to eosinophilic, ulcerative and necrotizing dermatitis; serocellular crust formation; and epidermal hyperplasia with dyskeratosis. Some lesions also had leucocytoclastic to eosinophilic vasculitis and thrombosis with ischaemic necrosis. Macroscopic and histological analyses confirmed the suspected ischaemic nature of the lesions but the specific aetiopathogenesis was elusive with a wide range of bacteria present, probably as opportunistic infections. However, Treponema spp and Orthopox virus were excluded as major aetiological agents. This study establishes a foundation for further investigations of the pathogenesis of bovine ITN and a basis for consistency in diagnosis and classification of the stage of disease. The findings are also key to further understanding disease progression and prognosis.